Luminescent Properties of a Cs3AlF6:Mn4+ Red Phosphor for Warm White Light-Emitting Diodes. (1st January 2018) - Ming, Hong; Zhang, Junfei; Liu, Lili; Peng, Jiaqing; Du, Fu; Ye, Xinyu
Abstract : Mn 4+ activated fluoride phosphors have been considered as highly promising red component for warm white light-emitting diodes (WLEDs) in recent years. In this work, a novel nonequivalent doping Cs3 AlF6 :Mn 4+ red-emitting phosphor were synthesized via a co-precipitation method and its crystal structure, morphology, and luminescent properties were investigated in detail. The Cs3 AlF6 :Mn 4+ phosphor with a sheet morphology have broad band absorption in blue light region (∼467 nm) and narrow bandwidth emissions in red region (∼634 nm). The WLED fabricated with Cs3 AlF6 :Mn 4+ red phosphor, YAG:Ce 3+ yellow phosphor and a blue InGaN LED chip demonstrates intense warm light with good luminescence performance of low related color temperature (CCT, Tc = 3659 K) and high color rendering index (CRI, Ra = 86.2). These results indicate the Cs3 AlF6 :Mn 4+ red phosphor can be a potential candidate for warm WLEDs.